Assessing the Family Hope Program's (PKH) Impact on Community Welfare through the CIBEST Method - Ulfatun Hasanah, Alief; Zakiyah Hastriana, Anna (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
This study analyzes the effectiveness of the Family Hope Program (PKH) in improving community welfare in Bragung Village, Sumenep District, through a holistic approach that combines material and spiritual aspects using the CIBEST model. Using a descriptive qualitative method, data was collected through participatory observation, in-depth interviews with 30 beneficiary families, and a study of official documents. The CIBEST model was applied to assess welfare through four dimensions: material-spiritual welfare, material poverty, spiritual poverty and absolute poverty. The research findings show that PKH succeeded in significantly improving welfare. The Welfare Index (W) increased from 0.267 to 0.8 (200%), while the Spiritual (Ps) and Absolute (Pa) Poverty Indices were eliminated. However, the Material Poverty Index (Pm) only fell by 25%, indicating the need to strengthen the economic aspects of the program. Theoretically, this research makes an innovative contribution by adapting the CIBEST model - originally for zakat programs - into a social policy evaluation instrument. This approach offers a new perspective in measuring well-being that is more comprehensive by integrating the spiritual dimension. The findings recommend: (1) strengthening community-based economic assistance programs, (2) improving synergies between social assistance programs, and (3) developing a monitoring system based on holistic indicators to ensure the sustainability of community welfare improvements.